Forging relationships to coproduce: A Consumer Commitment Model in an extended service encounter. (July 2016) - Guo, Lin; Chen, Cuiping; Xu, Huimin
Abstract: Consumer commitment is essential to ensure the service success in extended and complex services, wherein the service drop-out rates are often appalling. To build a more robust consumer commitment theory and provide solutions for the critical issue of high service drop-out rates in complex and extended services, this study develops a model of consumer commitment and tests it using survey data from consumer clients in a national debt management program in the U.S. The results reveal that calculative commitment only leads to consumers' intention to remain, whereas affective commitment leads to a broader range of coproduction behaviors (i.e., individual initiative and civic virtue). Moreover, besides consumers' relationship investment, perceived organizational support enhances both types of consumer commitment. It also increases consumer compliance. This study contributes to the consumer commitment theory by examining additional drivers and behavioral outcomes of commitment and by revealing the differential effects of different types of commitment on behavioral outcomes. Highlights: Consumers' relationship investment leads to not only calculative commitment but also affective commitment. Affective commitment drives both individual initiative and civic virtue. Calculative commitment only drives intention to remain. Consumers do not need to be affectively committed to the organization to comply with its requests. Consumers need to develop affective commitment to engage in civic virtue behaviors.